Python yu ce fen xi shi zhan = Hands-on predictive analytics with Python / = Hands-on predictive analytics with Python - Fuentes, Alvaro (Ren min you dian chu ban she = Posts & Telecom Press, 2022)
Detailed summary in vernacular field.
880-05;Ben shu you Yingguo Packt Publishing gong si shou quan Ren min you dian chu ban she chu ban
Keywords: Python (Computer program language); Application software -- Development; Decision making -- Data processing; Data mining; Big data; Python (Langage de programmation); Logiciels d'application; Développement; Prise de décision; Informatique; Exploration de données (Informatique); Données volumineuses